The junior encyclopedia of Islam - Khan, Saniyasnain; Erfani, Mohammad Imran (Goodword for Kids Delhi, 2013)
"The Junior Encyclopedia of Islam" by Saniyasnain Khan provides a child-friendly overview of key concepts, figures, and practices in Islam, making it accessible and engaging for young readers.